The Chemistry of 700 Years of Precipitation at DYE-3, Greenland. - Cragin,J. H.; Herron,M.; Langway,C. C. , Jr (1975)
Concentrations of sodium, potassium, magnesium, calcium, silicon, aluminum, lead and sulfate were measured in surface snow and in individual annual accumulation layers from a 373-m-deep ice core from Dye 3, Greenland (65 deg 12 min N, 43 deg 47 min W), covering the time period from 1232 to 1971 A.D. Average background (pre-1840) concentrations in micrograms/liter were determined. Observed concentrations of sodium, potassium, magnesium, calcium, silicon and aluminum can be adequately explained by relative abundances of these elements in seawater and terrestrial dust. Late 19th century annual ice layers contain twice as much sulfate as pre-1840 deposits, reflecting the increased use of fossil fuels in the Northern Hemisphere. Lead concentrations in post-1955 snow deposits are more than an order of magnitude greater than pre-1840 baseline concentrations and are attributed to smelting and the increased use of lead alkyls in gasoline. Errata sheet insertederted.